The Early Reception and Appropriation of the Apostle Peter (60-800 CE) The Anchors of the Fisherman - Dijkstra, Roald (Euhormos: Greco-Roman Studies in Anchoring Innovation, 2020)
The Early Reception and Appropriation of the Apostle Peter (60-800 CE) investigates the interdisciplinary history of the reception of Peter from the first century up to Charlemagne, revealing as much about Peter as about the context in which this reception took place. Readership: All interested in the art, culture, epigraphy, literature and politics of early Christianity/late antiquity and the reception of the figure of the apostle Peter in those areas.